Comparison of Quality of Life Between Fun Run and Slo-Pitch Communities in Bandung City - Haidir, Erik Dwi; gumilar, agus; Mudjihartono, Mudjihartono (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2025)
This study aimed to compare the quality of life between members of the Fun Run and Slo-Pitch sport communities in Bandung City. A cross-sectional comparative study design was employed involving 125 participants, consisting of 65 Fun Run members and 60 Slo-Pitch members, selected through purposive sampling. Quality of life was measured using the WHOQOL-BREF instrument, which assesses physical, psychological, social, and environmental domains. Data were analyzed using descriptive statistics and an independent samples t-test. The results showed that the mean quality of life score of the Fun Run community (M = 92.9) was slightly higher than that of the Slo-Pitch community (M = 91.7); however, the difference was not statistically significant (p = 0.585). These findings indicate that there is no significant difference in overall quality of life between the two communities despite differences in activity characteristics. Given the cross-sectional nature of the study, the findings should be interpreted descriptively and do not imply a causal relationship. Further studies using longitudinal or mixed-methods designs are recommended to explore the underlying mechanisms linking community-based physical activity and quality of life.